The Impact of Discoverys Learning Model for the Result of Social Subject Grade VIII SMP Swasta Bina Guna Tanah Jawa - Sartika Situmorang; Anggun Tiur Ida Sinaga; Injen Pardamean Butarbutar (International Journal of Integrated Science and Technology, 2023)
​The problem in this research is Learning outcomes on interaction material between ASEAN countries using the discovery learning model and the conventional model for class VIII at Bina Guna Tanah Java Private Middle School. ​This type of research is quantitative research . The population in this study were all students in class VIII of Bina Guna Tanah Java Private Middle School with a total of 66 students. The sample in this study consisted of 2 classes, namely class VIII-1 and class VIII-2 with a total of 66 students. ​Based on the results of descriptive analysis, it shows that the average social studies learning outcomes for students in classes that do not use the discovery learning model is 71.76. Meanwhile, the average student learning outcomes in classes that use the discovery learning model is 73.91. The results of inferential statistics using SPSS version 21 obtained Sig(2 Tailed)<α or (0.000<0.05) and the calculated t value > t table (3.818>1.294). So, based on the testing criteria, it can be said that there is a significant difference in learning outcomes between classes that use the discovery learning model and classes that use the conversion learning model in class VIII Anatar Nagara-ASEAN Countries Interaction material in social studies subjects at Bina Guna Tanah Java Private Middle School.